Spatial Contrast Sensitivity to Polarization and Luminance in Octopus - Nahmad-Rohen, Luis; Vorobyev, Misha (Frontiers in Physiology, 2020)
While colour vision is achieved by comparison of signals of photoreceptors tuned to different parts of light spectra, polarisation vision is achieved by comparison of signals of photoreceptors tuned to different orientations of the electric field component of visible light. Therefore, it has been suggested that polarisation vision is similar to colour vision. In most animals that have colour vision, the shape of luminance contrast sensitivity curve differs from the shape of chromatic contrast sensitivity curve. While luminance contrast sensitivity typically decreases at low spatial frequency due to lateral inhibition, chromatic contrast sensitivity generally remains high at low spatial frequency. To find out if the processing of polarisation signals is similar to the processing of chromatic signals, we measured the polarisation and luminance contrast sensitivity dependence in a colour-blind animal with well-developed polarisation vision, Octopus tetricus. We demonstrate that, in Octopus tetricus, both luminance and polarisation contrast sensitivity decrease at low spatial frequency and peak at the same spatial frequency (0.3 cpd). These results suggest that, in octopus, polarisation and luminance signals are processed via similar pathways.